Determining The Number of Machine at Seize Car Wash and Detailing Using Simulating Method - Kurnia, Johan; Basri, Mursyid Hasan (The Indonesian Journal of Business Administration, 2013)
Seize car wash and detailing started its business in 2009. At that moment Seize starting a business car wash with 2 hydraulic washer unit. Beginning in 2011 the owner of the car wash and detailing Seize plans to increase the number of washing machine hydraulics by 3 units, bringing the total hydraulic washing machine there are 5 units. In April 2011, Seize car wash and detailing has begun to operate using 5 units of hydraulic washing machine simultaneously. After the addition of the washing machine, the queue consumers appear significantly reduced. Additional machines to minimize the queue, caused another problems instead. At certain days when the customers are few, the 5 machines are in standby to anticipate customers. While in fact at those certain days some of the machines are not operated at all. These idle machines actually adding costs for the company. On the other hand, when it’s on peak even 5 machines are not enough. This is indicated by a long queue of customers on those days. These lead to the question of whether Seize’s capacity too small? Or is it too large already? Operational time Seize car wash and detailing starts at 08:00 until 18:00, the total time is 10 hour operations. Based on the calculations (ideal condition), Seize is capable of serving up to 100 customers each day. The study for this case using queuing theory and will be done using simulation method with igrafx, which will analyze changes of the capacity to the amount of customers. The simulation showed that if the average customer interval is every 15 minutes, the required capacity is 3 machines on standby.Keywords: capacity, utility, queuing, simulation, car wash.